A Study of the Nutritional Behavior and Body Mass Indexes for Students of Age (17-25) Years In Baghdad, Iraq. (Baghdad Science Journal, 2009)
The aim of this study was to assess the nutritional status for samples at the age of 17-15 years. These samples were taken from secondary schools and universities in Baghdad area, 123 of them were male and 261 were female. Data on weight, height and body mass index (BMI) were determined in each individual. Smaller sample of 215 individuals (male and female) from the original sample was taken in order to record their nutritional behavior and daily food intake during the 24 hours prior to the visit through personal meeting using special questionnaire. The results showed that the weight and the height were within the range of the people of neighboring Arab countries, who are in the same age. Beside 44.4- 55.95% of these samples were within the normal weight using body mass index. Percentages of obesity and overweight were between 43.5- 6.5% for male and female respectively. There was an increase in daily food intake in general for essential diet and energy indeed, as recorded in nutritional behavior. 67% of samples have their breakfast every day. There were 51% of the samples having snacks (additional meal) between the major meals everyday and 62% have beverages every day. Also high percentage of samples were having milk and its products, vegetables, fruits (as nutritional sources) every day and the percentages were 47%, 67%, 78% respectively. In general their nutritional behavior and daily food intake were within the limits which showed by American recommended daily dietary, still there was some incorrect nutritional behavior which need more education and learning about nutrition.